2013
DOI: 10.2147/dmso.s52166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a recreational physical activity and healthy habits orientation program, using an illustrated diary, on the cardiovascular risk profile of overweight and obese schoolchildren: a pilot study in a public school in Brasilia, Federal District, Brazil

Abstract: IntroductionEducative strategies need to be adopted to encourage the consumption of healthy foods and to promote physical activity in childhood and adolescence. The effects of recreational physical activity and a health-habit orientation program using an illustrated diary on the cardiovascular risk profile of overweight and obese children was investigated.MethodsThe weight and height of 314 schoolchildren aged between 9 and 11 years old, in a public school in Brasilia, Federal District, Brazil, were recorded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Atividades recreativas são também eficientes para promover a atenuação dos fatores de risco da obesidade infantil. Militão et al 37 acompanharam 34 escolares obesos entre 9 e 11 anos, durante o período de intervalo entre aulas. O estudo demonstrou que um programa de 10 semanas de exercício recreativos aliado a um programa de orientação de hábitos de vida saudáveis foi capaz de aumentar os valores de o VO2 max e reduzir os valores de LDL, triglicérides, colesterol total e pressão arterial.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Atividades recreativas são também eficientes para promover a atenuação dos fatores de risco da obesidade infantil. Militão et al 37 acompanharam 34 escolares obesos entre 9 e 11 anos, durante o período de intervalo entre aulas. O estudo demonstrou que um programa de 10 semanas de exercício recreativos aliado a um programa de orientação de hábitos de vida saudáveis foi capaz de aumentar os valores de o VO2 max e reduzir os valores de LDL, triglicérides, colesterol total e pressão arterial.…”
Section: Resultsunclassified
“…Recreational activities are also effective to promote the attenuation of risk factors of childhood obesity. Militão et al 37 followed 34 obese schoolchildren between 9 and 11 years during the interval between classes. The study demonstrated that a 10-week program of recreational exercise combined with a program promoting healthy lifestyle habits was able to increase the values of VO 2max , reduce LDL, triglycerides and total cholesterol as well as blood pressure levels.…”
Section: Effect Of the Types Of Physical Exercisesmentioning
confidence: 99%
“…Metabolic benefits include lowering blood pressure, reduction of leptin, glycemia, and insulin resistance, improved lipid profile with lowering of TC, and increased HDL-C [151,152]. The physical activity reduces the levels of these inflammatory cytokines leading in addition to increasing anti-inflammatory cytokines, such as interleukin 10 and adiponectin, even without modifying diet or lifestyle changes [153][154][155].…”
Section: Physical Exercisementioning
confidence: 99%
“…1 Sedentary behaviour "Switch Off-Get Active", health education intervention aimed to increase physical activity at the expense of screen time [ 180,182,[187][188][189][190]192,195,207,211,216,217,219,221,225,227,[231][232][233]237,241,243,245,247,248,[252][253][254][255][258][259][260][261][262]266,270,278,282,283,289,291,296,299,301,302]. Studies that were applicable to multiple themes were replicated within appropriate categories and account for the overlap in the total number of clinical trials.…”
Section: Clinical Trialsmentioning
confidence: 99%